Fear of disasters within the risk communication network of foreign students in Japan amid the COVID-19 pandemic crisis: A cohort design. (March 2022) - Dao, Minh Tuan; Lim, Seunghoo
Abstract: The main objective of this study is to examine the role of risk communication during the COVID-19 crisis, which is often neglected in studies investigating the outbreak of the pandemic. The study is based on survey data from a group of international (non-Japanese) students in Japan and the theoretical foundation of fear appeal theory. The results, which are based on the panel data structure, show that individually, (1) the act of seeking out others to discuss risks in depth in the current pandemic context or (2) the observed adoption of advocated precautionary health behaviours is not necessarily a good indicator of mental management, but (3) the combined effect of (1) and (2) unexpectedly suggests a conciliatory effect on the fear of disasters. Moreover, this evidence-based finding (3) suggests that a reciprocal relationship exists between threat and efficacy in terms of mediating fear under the framework and theory of fear appeals, indirectly challenging the fear control response proposition of the extended parallel process model. Our empirical findings emphasize the role of risk discourse and information sharing combined with preventive health behaviours adopted within a community in the context of global health crises. Highlights: This paper suggests implications for foreign students studying in Japan facing the unprecedented situation of COVID-19. Simply adopting health preventive measures as recommended can signal an increasing general fear of disasters. Risk communication at face value also indicates a worsening of the fear of disasters. The interactive effect of citizens' risk deliberation and the adoption of preventive health practices jointly alleviates anxiety about disasters. This paper provides empirical evidence for the extended parallel process model in the context of COVID-19.